Perbedaan Kemampuan Berpikir Spasial antara Siswa IPA dan IPS - Lathifa Yuliartiwi; Wahyu Widiyatmoko (Jurusan Pendidikan Geografi FKIP Universitas Halu Oleo, 2025)
Spatial thinking ability is an individual's capacity to identify problems, find answers, and communicate solutions by expressing relationships through media within a spatial structure. This research aims to analyze the spatial thinking ability between Science and Social Science students at Senior High School Muhammadiyah 1 Karanganyar, and to examine the differences in spatial thinking ability between these two groups of students. The research uses a quantitative method with a comparative design. The sample consists of 393 students from grade XII IPA and XII IPS at Senior High School Muhammadiyah 1 Karanganyar. Data collection was conducted using primary data through the Spatial Thinking Ability Test. The data analysis technique used the Mann-Whitney U test. The results show that Science students have an average spatial thinking ability score of 40.29, which falls into the moderate category, while IPS students have an average score of 35.96, which falls into the low category. Based on the Mann-Whitney U test, the significance value is 0.00 < 0.05, indicating a significant difference in spatial thinking ability between Science and Social Science students at Senior High School Muhammadiyah 1 Karanganyar. These findings highlight the need for integrating spatial thinking development into the educational curriculum.